2002
DOI: 10.5194/hess-6-983-2002
|View full text |Cite
|
Sign up to set email alerts
|

Nearshore circulation revealed by wastewater discharge from a submarine outfall, Aveiro Coast, Portugal

Abstract: Nearshore circulation revealed by wastewater discharge from a submarine outfall, Aveiro Coast, Portugal 983Hydrology and Earth System Sciences, 6(6), 983-989 (2002) AbstractThe morphological and climatic conditions of the Atlantic coast of northern Portugal result in a prevailing upwelling circulation over the continental shelf. A submarine outfall releases wastewater into the ocean c. 3 km directly offshore (at ~16 m water depth) from S. Jacinto, 5 km to the north of the inlet to the estuarine coastal lago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The prevailing inshore water current along the Aveiro coast is to the south. In a study on the Ria de Aveiro wastewater outfall using aerial observations and in situ water sampling, Figueiredo da Silva et al (2002a, b) observed no offshore transport of the wastewater plume, but most commonly transport in the direction of the lagoon inlet channel. This suggests that impacts of pollutants discharged can be anticipated in nearshore waters and potentially within the estuarine system (Figueiredo da Silva et al 2002a).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevailing inshore water current along the Aveiro coast is to the south. In a study on the Ria de Aveiro wastewater outfall using aerial observations and in situ water sampling, Figueiredo da Silva et al (2002a, b) observed no offshore transport of the wastewater plume, but most commonly transport in the direction of the lagoon inlet channel. This suggests that impacts of pollutants discharged can be anticipated in nearshore waters and potentially within the estuarine system (Figueiredo da Silva et al 2002a).…”
Section: Methodsmentioning
confidence: 99%
“…The wastewater treatment facilities in the estuary were built relatively recently, and until 2000, the effluents were discharged directly into the lagoon. Presently, all legal sources of effluent discharge are directed towards the ocean via a submarine outfall, which discharges domestic (30%) and industrial (70%) effluents after secondary treatment into the coastal area at 3.3 km offshore, 5 km north of the lagoon inlet (Figueiredo da Silva et al 2002a ). The prevailing inshore water current along the Aveiro coast is to the south.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Garvine (1987) classified plumes as supercritical or subcritical using the ratio of horizontal discharge velocity to internal wave phase speed and he later proposed (Garvine, 1995) a classification system based on bulk properties of the buoyant discharge. Referenced plume studies present numerical modelling of the case, in situ observations (Sherwin et al, 1997;Warrick & Stevens, 2011;Ogston et al, 2000), satellite observations (Di Giacomo et al, 2004;Nezlin and Di Giacomo, 2005;Molleri et al, 2010) or aerial photographs (Figueiredo da Silva et al, 2002;Burrage et al, 2008). In several cases two techniques are coupled (O'Donnell, 1990;Stumpf et al, 1993;Froidefond et al, 1998;Siegel et al, 1999).…”
Section: Introductionmentioning
confidence: 99%